Microinvasive Oral Squamous Cell Carcinoma Redefined by Using Modified Cajal Trichrome Differential Stain − A Histochemical Study - Vaishnavi Srinivasan; Gundamaraju Kiran Kumar; Naragani Durga Venkata Naga Shyam; Vaishali Narayen; Paremala Konda; Korra Swetha Rani (Wolters Kluwer Medknow Publications, 2022)
Introduction: In histopathologic laboratories, hematoxylin and eosin (H and E) staining is the routine and gold standard technique employed for biopsy tissues. But, few differential stains are being used in questionable diagnostic cases of oral squamous cell carcinoma (OSCC) to confirm its final diagnosis. Modified Cajal trichrome stain (CTS) is one such stain which may be employed as an adjunctive supporting aid for arriving at a conclusive diagnosis. To assess epithelial and connective tissue components in normal oral mucosa, oral epithelial dysplasia (OED), and OSCC cases stained with routine H and E and modified CTS. And also to compare and evaluate the efficacy of Modified CTS with that of H and E stain. Materials and Methods: A total of 40 tissue samples, 10 each of normal oral mucosa and OED, 20 cases of OSCC (10 cases each of microinvasive and frank OSCC) were stained with standard H and E and modified CTS simultaneously. Results: Modified CTS showed statistically significant and better results in differentiated terms of parameters such as depth of tumor invasion and differentiation between epithelial and connective tissue components in OSCC cases. Epithelial basement membrane interface and microinvasion are clearly appreciated in challenging cases of early epithelial malignancies such as microinvasive OSCC using this stain. Conclusion: As this stain can easily delineate epithelial structures from various connective tissue components, it may be utilized as an auxiliary diagnostic support along with routine H and E stain for confirmatory diagnosis.